The Evaluation of the Multimedia Coursebook Material in Listening 1 Course: Audio, Video, and Interactive Activities - Yella Dezas Perdani (Lingua Cultura, 2023)
The research aimed to evaluate the multimedia coursebook materials that had been applied in the Listening 1 course at one university in Indonesia, to know whether the coursebook used was presented well and still suitable to the student’s needs. The audio, video, and interactive activity provided in multimedia coursebook materials needed to be evaluated to determine their suitability for students, lecturers, and the institution. A qualitative method was applied, and the evaluation form was used to gather the data from two linguists of English Applied Linguistics, one Listening 1 lecturer, three students who had used the coursebook, and three students who had not used them. The data were summarized, analyzed, and qualitatively described. The finding shows that the audio, video, and interactive activity in the multimedia coursebook material applied in the Listening 1 course are presented well. To begin with, the audio provided is clear, and the accent is understandable. Then, the clarity of the video’s image, gestures, and facial expressions aid the students’ comprehension of the video’s content. The material, exercise, the application needed, and the link provided in the interactive activity are varied and appropriate to student needs and level of ability. The evaluation result can be used to improve the quality of multimedia coursebook material in the Listening 1 course. Finally, the research has the practical application of facilitating students’ learning needs by offering learning media resources in the form of multimedia coursebook materials.